Documentation of rare bird, Lesser White-fronted Goose, June 11, 1998, Jim Fuller - Fuller, James L.et al (1998)
Jim Fuller documents the sighting of a Lesser White-fronted Goose on June 11, 1998. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1998.